2015
DOI: 10.1007/s15010-015-0847-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting mortality in burn patients with bacteraemia

Abstract: In addition to conventional risk factors, recurrence and organ dysfunction at the onset of bacteraemia are also associated with mortality, while the pathogen involved is not a prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
1
14
2
Order By: Relevance
“…In developed nations, the ageing individuals are the fastest growing populations especially in Europe and America [6]. In addition, the mean age of burn patients admitted for burn injury in developed nations of Canada and Spain was higher than 44.7 and 53 years old respectively [7, 8]. In comparison with a population from a developing nation of Ecuador, the injured were younger patients with a mean age of 33 years [9].…”
Section: Introductionmentioning
confidence: 99%
“…In developed nations, the ageing individuals are the fastest growing populations especially in Europe and America [6]. In addition, the mean age of burn patients admitted for burn injury in developed nations of Canada and Spain was higher than 44.7 and 53 years old respectively [7, 8]. In comparison with a population from a developing nation of Ecuador, the injured were younger patients with a mean age of 33 years [9].…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently, Huang et al [16] developed a mathematical model of predicting mortality based on the admission characteristics including gender, age, the total burn area, the full thickness burn area, the inhalation injury, shock, and the period before admission in 6220 burn cases. Ceniceros et al [17] investigated the factors associated with mortality in burn patients and reported that age, the burn extent, and the SOFA score at the onset of bacteremia and recurrent bacteremia were significantly associated with the mortality. We did not investigate the bacteremia status of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus causes burn wound infection and failure of the skin graft, but seldom leads to mortality. Ceniceros et al (2015) conducted a retrospective study of adult patients with bacteremia and found that 17.5% of cases could be ascribed to Pseudomonas aeruginosa and 15.5% to Klebsiella pneumonia. S. aureus was the second most common cause of bacteraemia (Ceniceros et al, 2015).…”
Section: Burnsmentioning
confidence: 99%
“…Ceniceros et al (2015) conducted a retrospective study of adult patients with bacteremia and found that 17.5% of cases could be ascribed to Pseudomonas aeruginosa and 15.5% to Klebsiella pneumonia. S. aureus was the second most common cause of bacteraemia (Ceniceros et al, 2015). The most frequently isolated fungus was Candida species, which was increased during the hospital stay and peaked within the third and fourth week (Macedo & Santos, 2006).…”
Section: Burnsmentioning
confidence: 99%